The effects of calcaneal posture on thoracolumbar alignment in a standing position - Yi, Jae-Hoon; Seo, Dong-Kwon; Kim, Seon-Chil; Jung, Sang-Woo (Journal of Physical Therapy Science, 2017)
[Purpose] Severe calcaneus misalignment is correlated with low back pain, and affects pelvic alignment. However, little has been published with regard to the influence of pronation and supination on trunk alignment. Therefore, the present study aimed to investigate the influence of calcaneal inversion on pelvic and trunk alignment. [Subjects and Methods] A 3-dimensional motion analysis system was used to assess pelvic and trunk alignment in 10 healthy male subjects with unilateral and bilateral calcaneus inversion. [Results] Medial and anterior tilting of the pelvis, and posterior tilting and lateral rotation of the trunk were observed. [Conclusion] Calcaneal inversion induces changes in the alignment of the pelvis and trunk. These changes may induce lumbar lordosis and body misalignment, leading to back pain.